RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS BAWANG MERAH(Allium ascalonicum L.) TERHADAP BERBAGAI SUMBER NITROGEN ORGANIK - Sugiyarto Sugiyarto; Meiriani Meiriani; Jasmani Ginting (Universitas Sumatera Utara, 2013)
The research had been conducted at Tanjung Sari, Medan at ± 25 m asl from April until June 2012.The research using factorial randomized block design with 2 (two) treatment factors. The first factorwas using of three variety namely : V1: Bima Brebes; V2: Kuning; V3: Sembrani. The second factorwas addiction of fertilizer as organic nitrogen source with four levels P0: control ; P1: biomass ofsoya 2.357,67 kg/ha; P2: vermicompost 3.252,55 kg/ ha ; P3: palm oil fruit bunch 2.121,90 kg/ha;P4: chicken manure 3.350,37 kg/ha. The results showed that the Sembrani variety had given thebest results on some parameters of growth and production. The using of biomass of soya 2.357,67kg/ha resulted diameters and weight of tubers were compared with the other organic fertilizers andcontrol. The interaction between the both of treatment was effected significantly on parameters wetweight of tuber per plot, dry weight of tuber per plot, diameter of wet tuber per clump and diameterof dry tuber per clump.Key words : varieties, organic nitrogen, shallot